Analysis of the «Seventh word» Abay in the light of religious texts - Палторе, Ыктияр (Journal of Oriental Studies, 2017)
The article discusses the «Seventh word» Abay. The analysis focuses on the fact that the main ideas of the seventh word intertwined with religious texts.